Komposisi Jenis Tumbuhan Bawah dan Sifat Tanah di Lahan Bekas Tambang Kapur dan Silika PT Holcim Indonesia Tbk - Cahyo Wibowo; Dadan Mulyana; Wiwi Wildasari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
Mining activities were carried out, causing damage on soils, increased rates of erosion, decline in productivity and stability of the land. The revegetation process takes a long time, so it needs to plant cover crop plants. The goal of planting cover crop is to protect the soil from erosion . This research aims to study the composition of understory vegetation, and its potential to function as cover crops on soil which contain lime and silica in PT Holcim Indonesia Tbk. Undergrowth vegetation which was dominant in the ex- mining land of silica and lime were Imperata cylindrica and Eleusine indica soil properties in both locations were categorized as not fertile. Key words: cover crop, diversity of species, mining, soil properties, understorey